الأقوال الضعيفة في العبادات من "متن الغاية والتقريب": باب الطهارة والصلاة أنموذجا = Weak opinions in worship from the book of Al-Ghāyah wa al-Taqrīb: a case study of the chapters of purity and prayer - Suhaimi, Abdul Hakim; Artalim Zaim, Muntaha (IIUM Press, 2023)
This research aims to study the weak opinions in the chapters of purity and prayer from Matn al-Ghāyah wa al-Taqrīb of Imam Abu Shujā’ al-Aṣfahānī in the light of the reliable opinions in the Shafīʽite School. This study will deal with the analysis of these opinions that the author chose for his book and the commentaries from later Shafīʽite scholars in the chapters of purity and prayer. What indicates the importance of this topic is that this book has become famous and spread in front of the Shafīʽite students, but they do not know the existence of these weak opinions - which were stipulated by the later Shafīʽite scholars – and also they believe that these opinions do not exist at all. This research will help them to understand the existence of these opinions. In this research, the researchers have followed three main approaches, namely: the inductive approach, the analytical approach, and the comparative approach. The study reached important results, including that the Matn al-Ghāyah wa al-Taqrīb, with its majesty and fame, was not free from weak opinions, and that there is no text written before al-Nawawī and al-Rāfi‘ī except that it contains weak opinions; and finally, the reliable opinions in the Shafīʽite school are what have been decided by the later Shafīʽite scholars.